Overview of mobile communication network authentication - Xinxin HU; Caixia LIU; Shuxin LIU; Wei YOU; Kang QIAO (网络与信息安全学报, 2018)
With the increasingly serious security situation of mobile communication network,it becomes an important issue about how to protect the privacy of legitimate users while providing high-quality communication services,and how to protect the carrier network from being invaded becomes an important issue in the field of mobile communication security.Authentication is an important means for users and networks to authenticate each other's legitimacy.Authentication methods are also evolving along with network evolution.Starting with the authentication methods of past mobile communication networks (GSM,CDMA,UMTS,LTE),the advantages and disadvantages of each generation of authentication technology are analysed,along with which the authentication technology and unified authentication technology of the fifth-generation (5G) mobile communication to be commercialized are emphatically analysed.In the last,reasonable prospect for the development of authentication technology in the future are proposed.